Penerapan Model Pembelajaran Two Stay Two Stray (TSTS) pada Mahasiswa Farmasi - Lija Oktya Artanti (University Of Darussalam Gontor, 2017)
This research aims to increase the ability of scientific work and the learning achievement of Basic Physics Course Pharmacy Students UNIDA Gontor through the implementation of cooperative learning model Two Stay Two Stray (TSTS) based on practicum. The approach used in this study is a qualitative approach that displays everything that happens naturally, is without any manipulation. This study includes classroom action research (PTK). Subject research is pharmacy students the first semester Class A Academic Year 2016/2017 totaling 30 students. Data collection techniques used in this study includes written tests, observation, interviews, and documentation. The stages of data analysis in this study consisted of three phases: (1) data reduction, (2) display data, and (3) conclusion. The results showed that the implementation of cooperative learning model of Two Stay Two Stray (TSTS) based practicum conducted in the Course of Basic Physics class A in Study program Pharmaceutical UNIDA Gontor can improve the ability of scientific work and achievement of learning physics. The ability of students overall scientific work has increased in the first cycle to the second cycle of 25.72%. The learning achievement increased in the first cycle to the second cycle of 20%.